Magnetic study on biodistribution and biodegradation of oral magnetic nanostructures in the rat gastrointestinal tract. Issue 32 (1st August 2016) - Martín, Miguel; Rodríguez-Nogales, Alba; Garcés, Víctor; Gálvez, Natividad; Gutiérrez, Lucía; Gálvez, Julio; Rondón, Deyanira; Olivares, Mónica; Dominguez-Vera, Jose M.
Abstract : Probiotic bacteria serve as carriers of magnetic nanoparticles to treat iron deficiency, assisting them to overcome the stomach and accumulate in intestines. Abstract : We have undertaken a magnetic study on the oral biodistribution and biodegradation of nude maghemite nanoparticles of 10 nm average size (MNP) and probiotic bacteria, Lactobacillus fermentum, containing thousands of these same nanoparticles (MNP–bacteria). Using AC magnetic susceptibility measurements of the stomach, small intestine, cecum and large intestine obtained after rat sacrifice, and iron content determination by ICP-OES, we have monitored the biodistribution and biodegradation of the maghemite nanoparticles along the gastrointestinal tract, after oral administration of both MNP and MNP–bacteria. The results revealed that the amount of magnetic nanoparticles accumulated in intestines is sensibly higher when MNP–bacteria were administered, in comparison with MNP. This confirms our initial hypothesis that the use of probiotic bacteria is a suitable strategy to assist the magnetic nanoparticles to overcome the stomach medium, and to achieve their accumulation in intestines. This finding opens doors to different applications. Since iron absorption in humans takes place precisely in the intestines, the use of MNP–bacteria as an iron supplement is a definite possibility. We have actually illustrated how the administration of MNP–bacteria to iron-deficient rats corrects the iron levels after two weeks of treatment.